(untitled) - Shaara, Jeff; 1952- (New York, 2024)
"From the bestselling author comes the story of rising conflict between the super-powers that gripped the world, a global war that almost happened: The Cuban Missile Crisis. In 1961, the new president John F. Kennedy, inherited an ill-conceived, poorly executed invasion of Cuba that failed miserably and set in motion the events that put the U.S. and the Soviet Union on a collision course that nearly started a war that would have enveloped much of the world. Extensively researched and vividly imagined, The Shadow of War brings to life the many threads that lead to the building crisis between the Soviet Union and the United States in 1962. Told from a multitude of perspectives and voices, from the Russian engineer attempting the near impossible task of building the missile launch facilities in Cuba, to the U.S. Navy commanders who ships are sent to "quarantine" Cuba, to the Soviet Premier, Nikita Khrushchev, desperately trying to maintain a challenging balancing act between the conflicting demands of various powerful forces, to the brothers Kennedy (Bobby and JFK) who can't allow Russia to land nuclear missiles in Cuba, or to appear weak in confronting Khrushchev, but keenly understand how close they are dancing to the edge of war. Shaara brings to life all the action and actors, famous and little known, that embodied a war that almost happened, the Cuban Missile Crisis"--
Keywords: Cuban Missile Crisis, 1962; Fiction; Historical fiction; Novels